2011
DOI: 10.1016/j.jcin.2011.01.010
|View full text |Cite
|
Sign up to set email alerts
|

30-Day Readmissions After Coronary Artery Bypass Graft Surgery in New York State

Abstract: The 30-day readmission rate for CABG surgery remains high, despite decreases in short-term mortality. Patients with any of the numerous risk factors for readmission should be closely monitored. Hospital readmission rates are not highly correlated with mortality rates and might serve as an independent quality measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
193
3
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(217 citation statements)
references
References 11 publications
16
193
3
5
Order By: Relevance
“…Although we found a significant relationship between the CTM-3 and readmission within the PCI and total populations, we did not find a statistically significant relationship in the more debilitated CABG population. This 18 and many readmissions are not easily attributable to a single cause. 1,19 Therefore, even if the three domains of the CTM-3 were addressed equally for patients with PCI and CABG, their post transition experiences and ultimate reasons for readmission could vary greatly.…”
Section: And Readmissionmentioning
confidence: 94%
“…Although we found a significant relationship between the CTM-3 and readmission within the PCI and total populations, we did not find a statistically significant relationship in the more debilitated CABG population. This 18 and many readmissions are not easily attributable to a single cause. 1,19 Therefore, even if the three domains of the CTM-3 were addressed equally for patients with PCI and CABG, their post transition experiences and ultimate reasons for readmission could vary greatly.…”
Section: And Readmissionmentioning
confidence: 94%
“…21,22 The existence of wide variability in previous studies, the substantial variation observed in the current report, and the very low readmission rates achieved by some programs, 23,24 all suggest opportunities for improvement.…”
Section: Significant Interhospital Variation In Cabg Readmission Ratesmentioning
confidence: 61%
“…Among New York CABG patients from 1999, the overall readmission rate was 15.3%; 12.9% of patients were readmitted for reasons that appeared directly related to surgery. 11 In a follow-up study of patients from 2005 to 2007, 21 the comparable rates were even higher (16.5% and 14.3%, respectively).…”
Section: Lack Of Improvement In Cabg Readmission Ratesmentioning
confidence: 92%
See 2 more Smart Citations